2013
DOI: 10.4236/ojmp.2013.24023
|View full text |Cite
|
Sign up to set email alerts
|

Racial Provocation Induces Cortisol Responses in African-Americans*

Abstract: Purpose: To examine salivary cortisol responses to a racially-charged stimulus in a group of African-American individuals. Methods: A nonrandom sample of 245 (age: 43.8  11.1 years; 64% female) African-American individuals was recruited by advertisements. Specifically, salivary cortisol was assessed prior to and after being exposed to a racially-charged movie clip. In addition, the salivary cortisol was assessed in the morning and evening of the day following exposure to the racially-charged movie clip. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Traditionally, researchers interested in social stigma and the HPA axis have speculated that stress resulting from stigmatized group membership may lead to hyper-reactivity. Although counter to these speculations, hypo-reactivity of the HPA axis following social stress among women higher in stigma consciousness is consistent with findings from work on other constructs related to social identity threat, including perceived discrimination (Weinstein et al, 2013) and exposure to structural stigma (Hatzenbuehler & McLaughlin, 2014), as well as other forms of stress and adversity (e.g., Carpenter et al, 2011; Elzinga et al, 2008; Lovallo et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…Traditionally, researchers interested in social stigma and the HPA axis have speculated that stress resulting from stigmatized group membership may lead to hyper-reactivity. Although counter to these speculations, hypo-reactivity of the HPA axis following social stress among women higher in stigma consciousness is consistent with findings from work on other constructs related to social identity threat, including perceived discrimination (Weinstein et al, 2013) and exposure to structural stigma (Hatzenbuehler & McLaughlin, 2014), as well as other forms of stress and adversity (e.g., Carpenter et al, 2011; Elzinga et al, 2008; Lovallo et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…Despite the theorized pathway to HPA activation, only a few studies have explored the association between direct ethnic discrimination and HPA activity (Cohen et al, 2006; Fuller-Rowell, Doan, & Eccles, 2012; Kaholokula, Grandinetti, Keller, Nacapoy, & Mau, 2012; Ratner, Halim, & Amodio, 2013; Richman & Jonassaint, 2008; Townsend, Eliezer, Major, & Mendes, 2014; Weinstein et al, 2013). To our knowledge, no studies have examined this association experimentally.…”
Section: Direct Ethnic Discrimination Is a Life Stressormentioning
confidence: 99%
“…In terms of HPA activity, one study found that recent exposure to a highly publicized racial incident is associated with a heightened stress response as demonstrated by elevated cortisol levels (Richman & Jonassaint, 2008). Similarly, viewing a racially charged movie clip was associated with increased cortisol production in African Americans (Weinstein et al, 2013). Given the mixed findings on cardiovascular response and scant evidence on HPA response to indirect ethnic discrimination, additional studies are needed to understand how these common experiences impact physiological reactivity.…”
Section: The Impact Of Indirect Discrimination On Health Is Less Clearmentioning
confidence: 99%
“…Given the major role that SNS and HPA axis play in responding to stress, much prior work has investigated the acute effects of racism on activity of these physiological systems. Indeed, laboratory studies have demonstrated pronounced cortisol reactivity in response to experimental manipulations of racism, including in response to anticipating interactions with a prejudiced cross-race/ethnicity partner (Sawyer et al, 2012), viewing or overhearing racially discriminatory content (Huynh et al, 2017; Weinstein et al, 2013), and experiencing social rejection by a presumed prejudiced evaluator (Townsend et al, 2014). Prior work has also demonstrated that racism-related stress may evoke a pernicious cardiovascular reactivity pattern characterized by elevated SNS activity and diminished parasympathetic nervous system activity (Sawyer et al, 2012).…”
Section: Effects Of Racism On Physiologymentioning
confidence: 99%